Restauração do concreto aparente: estudo tecnológico para salvaguarda de edificações com tendências modernistas - OLIVEIRA, Djanira Cabral Viégas Borges da Cruz (Universidade Federal do Pará, 2014)
Concrete is basically formed by mixed cement, water, sand and stone, and has emerged as a building material to replace wood, stone, brick and even structural steel, but only in the twentieth century its aesthetic beauty was recognized. The modernism appropriated the new constructive technology and its plastic possibilities and splited definitively with the passed styles. Influenced by the schools of Rio and São Paulo, architects and engineers who built at Belém left a legacy of unfinished concrete constructions, which unfortunately is being threatened by the lack of specific care, since many interventions are made in a random and misguided way. Therefore, the aim of this research is to study the unfinished concrete under the historical and technological aspects in order to develop a methodology for restoration of areas with gaps, considering aspects such as color, texture and strength, seeking a compatible material to the original concrete. The study was conducted in three different steps: 1) Historical Research, 2) Field Research; 3) Research Laboratory. The materials of this study correspond to samples collected in three buildings and laboratory samples. The physical characterization of the samples allowed to find the approximated trace of the old concrete of 1:3 and the strength of the material, which is approximately 22MPa. The chemical and mineralogical characterization indicated that the original material has been suffering process of mineralogical transformation evidenced by the presence of polymorphs of calcium carbonate (CaCO3) and allowed to understand that the aggregates used in the composition of the material may have quartz or gravel origin. It was also observed that the color and texture of the material varies depending on the type of cement and aggregate used in the production of concrete. From the identification of the principle features of the original materials was developed a methodology for producing a mortar for restoration with properties similar to the antique material. The results as color, texture, and strength were satisfactory, because the values established by rule were accomplished and were also compatible to the appearance of the original concrete, allowing restoring the image of the building and achieving the proposed objectives.